2003
DOI: 10.1007/s11940-003-0022-z
|View full text |Cite
|
Sign up to set email alerts
|

Current complementary and alternative therapies for multiple sclerosis

Abstract: The use of complementary and alternative medicine (CAM) appears to be high in the general population and in patients with multiple sclerosis (MS). There are no diets or dietary supplements that are definitely effective in altering the disease course in MS. However, diets and dietary supplements that increase the intake of polyunsaturated fatty acids may produce mildly beneficial effects. Because these approaches are not definitely effective, they may be of limited interest to physicians and other conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Generally, patients decide on using CAM in the absence of clinical research. It should, however, be stated that not all CAMs are harmless, because there are findings in the literature that indicate potential risks and side effects, for example caused by phytotherapy (herbal medicine) [10] and dietary supplements [6,7].…”
Section: Annett Apel Brigitte Greim Nicolaus König Uwe K Zettlmentioning
confidence: 99%
“…Generally, patients decide on using CAM in the absence of clinical research. It should, however, be stated that not all CAMs are harmless, because there are findings in the literature that indicate potential risks and side effects, for example caused by phytotherapy (herbal medicine) [10] and dietary supplements [6,7].…”
Section: Annett Apel Brigitte Greim Nicolaus König Uwe K Zettlmentioning
confidence: 99%
“…Information on concomitant use of CAM is essential as some of these treatments are associated with side effects and might interact with conventional chemotherapy [29,30]. Several authors have reported potential risks and side effects, for example, caused by phytotherapy, herbal medicine [14], and dietary supplements [5]. A stimulating effect of mistletoe extracts on leukemic cells from patients with CLL has been discussed [38].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the widespread use, studies on risks associated with the use of CAM still remain sparse, and a need for more research that enables patients to make informed treatment decisions has been emphasized by several authors [14][15][16][17][18][19][20][21][22][23][24]. The existing literature shows that benefits and low risk are associated with some specific CAM treatments used by MS and cancer patients when implemented properly [e.g., 14-16, 19, 25-27], while other treatments are considered unsafe or ineffective [e.g., [14][15][16]18]. In general, increased CAM use has been interpreted as a result of both a positive attitude toward CAM and a somewhat negative attitude toward conventional health care.…”
Section: Cam and Riskmentioning
confidence: 99%